The predictive value of Naples prognostic score for patients with locally advanced non-small cell lung cancer undergoing surgery after neoadjuvant chemotherapy - Zhang, Yanfei; Tang, Chunyan; Yang, Min; Li, Shixuan; Li, Fangchao; Wang, Yang; Qi, Li; Li, Jingjing (Frontiers in Immunology, 2025)
ObjectiveTo evaluate the prognostic significance of the Naples Prognostic Score (NPS) in patients with locally advanced non-small cell lung cancer (NSCLC) after neoadjuvant chemotherapy and surgery.MethodsA retrospective review was done of 126 patients with locally advanced NSCLC who were surgically treated Affiliated Hospital of Weifang Medical University. from September 2012 to April 2019. According to the neutrophil-to-lymphocyte ratio (NLR), lymphocyte-to-monocyte ratio (LMR), albumin, and total cholesterol before neoadjuvant chemotherapy, NPS was divided into separate groups: group 0, group 1, and group 2. Kaplan-Meier method was used to analyze survival curves for the NPS. Univariate and multivariate Cox analysis of overall survival (OS) and progression-free survival (PFS) was then conducted.ResultsThis study included 60 male and 66 female patients, with the median age being 59 (59.94 ± 11.77). Based on the NPS system, the three groups were divided: Group 0, 41(32.5%) patients; Group 1, 55(43.7%) patients; and Group 2, 30(23.8%) patients. Smoking status (P=0.032) and KPS score (P=0.018) were significantly different among the three NPS groups, but it had no statistical relevance in regards to gender (P=0.849), age (P=0.474), clinical stage (P=0.101), pathology (P=0.819), tumor location (P=0.304), degree of differentiation (P=0.889), surgical method (P=0.436), chemotherapy (P=0.718), postoperative complications (P=0.177) or CEA level (P=0.447). Univariate Analysis showed that clinical stage (P=0.004), KPS score (P=0.003), surgery approach (P=0.042) and NPS (Group 2 vs. Group 0, P< 0.001; Group 1 vs. Group 0, P=0.005) were predictors of OS in patients with locally advanced NSCLC, and that clinical stage (P=0.005), KPS score (P=0.002), and NPS (Group 2 vs. Group 0, P< 0.001; Group 1 vs. group 0, P=0.001) were significantly associated with PFS. Based on the positive results of univariate analysis, we performed multivariate analysis. Multivariate Cox Regression showed that the NPS was a significant independent predictor of worse OS (Group 2 vs. Group 0, P=0.006; Group 1 vs. group 0, P=0.017) and PFS (group 2 vs. group 0, P=0.006; Group 1 vs group 0, P=0.011).ConclusionAs a clinically accessible blood indicator, NPS has vital value in predicting the prognosis of resected locally advanced NSCLC patients receiving neoadjuvant chemotherapy and surgery.